Labour market projections and time allocation in Myanmar: Application of a new computable general equilibrium (CGE) model - Henning Tarp Jensen; Marcus Keogh-Brown; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Myanmar has, in recent years, strengthened its focus on human capital as a development pillar, and introduced legislation and adopted conventions on child labour. But child exploitation continues, including use of forced labour by the military and children performing hazardous work. Moreover, Myanmar faces a rapidly closing window of opportunity within which to train its workforce to meet the future challenges of declining population growth and an ageing society. To address the twin challenges of child exploitation and future labour market needs, we study a comprehensive stylized education reform package for child workers aged 10-14. We employ a newly developed dynamically recursive 2021-40 computable general equilibrium model for Myanmar to analyse the economic and household income distribution impacts of a combined child work elimination and education programme allowing current child workers to achieve the same distribution of educational attainment as wider society over a 15-year transition period. While child work elimination would be costly for disadvantaged rural households, the combined programme may leave them better off, though only after a long transition period. At the societal level, the opportunity costs of child work elimination outweigh the long-term economic benefits of education over our 20-year horizon. In spite of the lack of societal economic benefits, our proposed reforms do seem to be advantageous, dealing with the unethical and appalling continuation of child labour practices while improving income distribution in favour of disadvantaged rural households. This would allow Myanmar to move towards the goal of SDG8, 'Decent Work and (Inclusive) Economic Growth', while training current generations to support an ageing Myanmarese society.
Keywords: C68; I25; J22; O2; 330; Myanmar; child labour; education reform; decent work; household income distribution